Reading Shakespeare's mind - Sohmer, Steve (Manchester University Press, 2017)
This book shows that William Shakespeare was a more personal writer than any of his innumerable commentators have realised. It asserts that numerous characters and events were drawn from the author's life, and puts faces to the names of Jaques, Touchstone, Feste, Jessica, the 'Dark Lady' and others.Steven Sohmer explores aspects of Shakespeare's plays and sonnets that have been hitherto overlooked or misinterpreted in an effort to better understand the man and his work. If you've ever wondered who Pigrogromitus was, or why Jaques spies on Touchstone and Audrey - or what the famous riddle M.O.A.I. stands for - this is the book for you.